Preparation of HMX/TATB Composite Particles Using a Mechanochemical Approach. Issue 2 (14th October 2015) - Wang, Zhixiang; Guo, Xiaode; Wu, Fei; Yan, Ting
Abstract: To improve the safety of HMX, HMX/TATB composite particles were prepared using a mechanochemical approach. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT‐IR) and X‐ray diffraction (XRD) were employed to characterize the HMX particles before and after being coated. The results showed that the HMX particles were coated by submicrometer‐sized TATB particles. The crystal form of HMX maintained unchanged during the whole preparing process. The decomposition characteristics of HMX/TATB composite were investigated by DSC, showing that the decomposition peak temperature increased by 5.141 °C, while the phase transition temperature decreased by 4.064 °C. Compared with the uncoated HMX particles, the impact and friction sensitivities were decreased by 56.1 and 70 %. Moreover, the grinding mechanism was investigated and discussed. Abstract :